What Matters for Electrification? Evidence from 70 Years of U.S. Home Heating Choices - Davis, Lucas W. (The Review of Economics and Statistics, 2025)
Abstract The percentage of U.S. homes heated with electricity has increased steadily from 1% in 1950 to 40% in 2020. Energy prices, geography, climate, housing characteristics, and income are shown to explain 90% of the increase, with energy prices by far the most important factor. The paper then estimates the cost of an electrification mandate for new homes. Households in warm states tend to prefer electricity anyway, so would be made worse off by less than $350 annually on average. Households in cold states, however, tend to prefer natural gas so would be made worse off by more than $1,000 annually.